MEMAHAMI NILAI RELIGIUSITAS DALAM KEPEMIMPINAN âAHOKâ SEBAGAI BENTUK REGULASI DIRI - Abadi*, M. Imron (Universitas Muhammadiyah Jember, 2016)
Values reflect a persons behavior in accordance with the norms and the rules t applied in religion. Religious interpreted as properties associated with religious values. Religiosity value refers to the values which guides human behavior to the right destination. Religiosities value is the concept of mans relationship to God, man to other man, and man to himself. Religiosity value cannot be separated from man behavior toward the truth and his behavior toward the rules of the religion. This study aims: (1) to understand the value of religiosity in âAhokâ leadership, (2) to determine the form of self-regulation in the leadership of âAhokâ. This study uses a qualitative approach using content analysis. Sources of data in this study comprise any recorded data related to Ahokâs performance; those data include any printed or electronic transcriptions of the mass media.This study examined the value of religiosity of âAhokâ concerning with (1) the religiosity relationship of Ahok to his God, (2) the religiosity relationship Ahok Â to the community, and (3) the religiosity relationship Ahok to himself. In addition, the form of âAhokâ leadership regulation comparises (1) receiving, (2) evaluating, (3) searching, (4) formulating, (5) implementing, and (6) assessing.Key words: Values, Religiosity, Leadership, Self-Regulation.